2014
DOI: 10.1002/anie.201408082
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for the In Vitro Production of Azol(in)e‐Based Cyclic Peptides

Abstract: Heterocycle-containing cyclic peptides are promising scaffolds for the pharmaceutical industry but their chemical synthesis is very challenging. A new universal method has been devised to prepare these compounds by using a set of engineered marine-derived enzymes and substrates obtained from a family of ribosomally produced and post-translationally modified peptides called the cyanobactins. The substrate precursor peptide is engineered to have a non-native protease cleavage site that can be rapidly cleaved. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 28 publications
2
81
0
Order By: Relevance
“…This work is complementary to a recent report wherein simple derivatives of the patellamide core sequence were synthesized in vitro (Houssen et al, 2014). Here, this work synthesizes highly distant sequences using the same set of enzymes, including a hybrid of modifications from different pathways.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This work is complementary to a recent report wherein simple derivatives of the patellamide core sequence were synthesized in vitro (Houssen et al, 2014). Here, this work synthesizes highly distant sequences using the same set of enzymes, including a hybrid of modifications from different pathways.…”
Section: Discussionsupporting
confidence: 54%
“…For several years, the ability to perform one-pot reactions eluded us and has proved challenging in other hands as well, where proteases other than PatA were required (Houssen et al, 2014). Here, we showed that this was due to differential redox sensitivity of various enzymes in the pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This required that if the preceding heterocyclization required DTT, then the heterocyclized product had to be purified for subsequent proteolysis. Alternatively, the protease cleavage site could be replaced to include a commercial protease cleavage site (Houssen et al, 2014), although this is not advantageous for one-pot synthesis. In addition, certain substrates that did not carry intramolecular disulphides could be easily processed by the heterocyclase without the need for reduction, and such substrates could be used in one-pot reaction schemes that could be modified to the final natural product carrying up to at least four posttranslational modifications (Sardar et al, 2015a).…”
Section: Synthesis Of Cyanobactins In Vitromentioning
confidence: 99%
“…Alternative routes to generate products and derivatives in vitro have also been reported, such as use of commercial protease cleavage sites in addition to cyanobactin enzymes (Houssen et al, 2014), use of posttranslational enzymes fused to substrate leader sequence (Oueis et al, 2015) and use of an in vitro translation platform (Goto et al, 2014). A unique feature of cyanobactin RiPP pathways that has enabled in vitro synthesis of cyanobactin derivatives is their modularity (Sardar et al, 2015a).…”
Section: Synthesis Of Cyanobactins In Vitromentioning
confidence: 99%
“…Another important potential application of this method is in synthetic biology efforts as RiPPs are well suited for generation of non-natural cyclic compounds/scaffolds that can be screened/selected for various purposes. 12,13 In this arena, there is no obvious inherent advantage or disadvantage whether the peptide contains an N-terminal amino or hydroxyl group at the start of the selection process. However, the ability to readily remove the leader peptide in a general manner without the need to screen various proteases is highly enabling.…”
mentioning
confidence: 99%